ASSOCIATION OF PLASMA ω-3 FATTY ACIDS WITH EARLY AGE-RELATED MACULAR DEGENERATION IN THE MULTI-ETHNIC STUDY OF ATHEROSCLEROSIS. Issue 7 (July 2022) - Karger, Amy B.; Guan, Weihua; Nomura, Sarah O.; Weir, Natalie L.; Klein, Barbara E.K.; Burke, Gregory L.; Johnson, W. Craig; Tsai, Michael Y.
Abstract : Supplemental Digital Content is Available in the Text. In this prospective multiethnic cohort study, there was a significant association between increasing plasma docosahexaenoic acid and increasing docosahexaenoic acid + eicosapentaenoic acid with reduced risk for early age-related macular degeneration. Our study represents the first racially diverse study to demonstrate an association between omega-3 fatty acids and age-related macular degeneration risk. Abstract : Purpose: To examine the association between omega-3 polyunsaturated fatty acids, docosahexaenoic acid, and eicosapentaenoic acid and age-related macular degeneration (AMD) in the Multi-Ethnic Study of Atherosclerosis cohort. Methods: Multi-Ethnic Study of Atherosclerosis is a multicenter, prospective cohort study designed to identify risk factors for cardiovascular disease in four ethnic groups. Six thousand eight hundred and fourteen participants of White, African American, Hispanic/Latino, and Chinese descent, aged 45–84 years, were recruited, with those found to have cardiovascular disease excluded. Our study population included all Multi-Ethnic Study of Atherosclerosis participants with baseline polyunsaturated fatty acid measurements and retinal photography at Examination 5 (n = 3, 772). Fundus photographs were assessed for AMD using a standard grading protocol. Relative risk regression (log link) determined associations between polyunsaturated fatty acid levels and AMD. Results: There was a significant association between increasing docosahexaenoic acid levels and increasing docosahexaenoic acid + eicosapentaenoic acid levels with reduced risk for early AMD (n = 214 participants with early AMD, of which n = 99 (46.3%) are non-White). Eicosapentaenoic acid levels alone were not significantly associated with AMD. Conclusion: Our analysis suggests increasing levels of docosahexaenoic acid are associated with reduced risk for early AMD in a multiethnic cohort. This represents the first racially diverse study demonstrating an association between omega-3 polyunsaturated fatty acids and AMD risk.